Self-Referential Cognition and Empathy in Autism - Lombardo, Michael V. (Public Library of Science, 2007)
BACKGROUND: Individuals with autism spectrum conditions (ASC) have profound impairments in the interpersonal social domain, but it is unclear if individuals with ASC also have impairments in the intrapersonal self-referential domain. We aimed to evaluate across several well validated measures in both domains, whether both self-referential cognition and empathy are impaired in ASC and whether these two domains are related to each other. METHODOLOGY/PRINCIPAL FINDINGS: Thirty adults aged 19-45, with Asperger Syndrome or high-functioning autism and 30 age, sex, and IQ matched controls participated in the self-reference effect (SRE) paradigm. In the SRE paradigm, participants judged adjectives in relation to the self, a similar close other, a dissimilar non-close other, or for linguistic content. Recognition memory was later tested. After the SRE paradigm, several other complimentary self-referential cognitive measures were taken. Alexithymia and private self-consciousness were measured via self-report. Self-focused attention was measured on the Self-Focus Sentence Completion task. Empathy was measured with 3 self-report instruments and 1 performance measure of mentalizing (Eyes test). Self-reported autistic traits were also measured with the Autism Spectrum Quotient (AQ). Although individuals with ASC showed a significant SRE in memory, this bias was decreased compared to controls. Individuals with ASC also showed reduced memory for the self and a similar close other and also had concurrent impairments on measures of alexithymia, self-focused attention, and on all 4 empathy measures. Individual differences in self-referential cognition predicted mentalizing ability and self-reported autistic traits. More alexithymia and less self memory was predictive of larger mentalizing impairments and AQ scores regardless of diagnosis. In ASC, more self-focused attention is associated with better mentalizing ability and lower AQ scores, while in controls, more self-focused attention is associated with decreased mentalizing ability and higher AQ scores. Increasing private self-consciousness also predicted better mentalizing ability, but only for individuals with ASC. CONCLUSIONS/SIGNIFICANCE: We conclude that individuals with ASC have broad impairments in both self-referential cognition and empathy. These two domains are also intrinsically linked and support predictions made by simulation theory. Our results also highlight a specific dysfunction in ASC within cortical midlines structures of the brain such as the medial prefrontal cortex.